Densely Populated Bismuth Nanosphere Semi‐Embedded Carbon Felt for Ultrahigh‐Rate and Stable Vanadium Redox Flow Batteries. Issue 37 (12th August 2020) - Zhou, Xuelong; Zhang, Xiangyang; Mo, Lanlan; Zhou, Xuechang; Wu, Qixing
Abstract: The elaborate spatial arrangement and immobilization of highly active electrocatalysts inside porous substrates are crucial for vanadium redox flow batteries capable of high‐rate charging/discharging and stable operation. Herein, a type of bismuth nanosphere/carbon felt is devised and fabricated via the carbothermic reduction of nanostructured bismuth oxides. The bismuth nanospheres with sizes of ≈25 nm are distributed on carbon fiber surfaces in a highly dispersed manner and its density reaches up to ≈500 pcs µm −2, providing abundant active sites. Besides, a unique bismuth nanosphere semi‐embedded carbon fiber structure with strong interfacial BiC chemical bonding is spontaneously formed during carbothermic reactions, offering an excellent mechanical stability under flowing electrolytes. It shows that the bismuth nanosphere semi‐embedded carbon felt can effectively promote V(II)/V(III) redox reactions with appreciable catalytic activity. The battery with the present electrode sustains an energy efficiency of 77.1 ± 0.2% and an electrolyte utilization of 57.2 ± 0.2% even when a current density up to 480 mA cm −2 is applied, which are remarkably higher than those of batteries with the bismuth nanoparticle/carbon felt synthesized by the electrodeposition method (62.6 ± 0.1%, 23.6 ± 0.2%). Further, the battery with the present electrode demonstrates a stable energy efficiency retention of 98.2% after 1000 cycles. Abstract : A densely populated bismuth nanosphere semi‐embedded carbon felt is devised and fabricated for vanadium redox flow batteries. The high‐density distribution of bismuth nanosphere and unique semi‐embedded structure render the flow battery a high energy efficiency at a ultrahigh charging/discharging rate up to 480 mA cm −2 and an extremely low energy efficiency decay rate within 1000 cycles.